INTERNATIONAL ECONOMIC INTEGRATION: SPECIFICITY AND PERSPECTIVES OF EURASIAN REGIONAL ASSOCIATIONS - I. Rogova; A. Palvanov (Вестник университета)
Thearticle analyses approaches of various schools,Russian and foreign economists to understanding of international economic integration. Eurasian integration projects are viewed as major driving forces of globalization. Current strategies of Eurasian regionalism and the role of Russia in this process is analyzed. Key tendencies and directions of integration in the global economy are examined. The article gives a detailed analysis of international economic unions and associations operating in the modern world.